How does mindfulness relate to benign/malicious envy? The mediating role of resilience, internal locus of control and self-esteem - Dong, Xia; Li, Xiaojun; Jiang, Xinsheng; Xiang, Yanhui (Frontiers in Psychiatry, 2022)
The present study aimed to explore the roles of resilience, internal locus of control, and self-esteem in the link between mindfulness and benign/malicious envy (BE/ME). 991 participants (299 males, 692 females; mean age =19.05 ± 1.54) completed a survey that assessed mindfulness, internal locus of control, resilience, self-esteem, and BE/ME. The results suggest that resilience, internal locus of control, and self-esteem independently mediate the relationship between mindfulness and BE/ME. Additionally, ‘internal locus of control → resilience’ and ‘self-esteem → resilience’ play chain mediating roles in the relationship between mindfulness and BE/ME. Namely, mindfulness is positively associated with resilience via improving internal control and self-esteem, thereby inhibiting malicious envy and promoting benign envy. The present study advances our knowledge of the mindfulness reperceiving theory, and thus provides a new explanation for the inhibition of negative emotions from the perspective of resilience, internal locus of control, and self-esteem.